Diagnóstico Del Sector Arrocero Del Departamento Del Meta Para Su Posible Participación En Proceso De Reapertura Comercial Entre Colombia y Venezuela (2022)
Carry out a diagnosis of the rice sector in the department of Meta for its possible participation in the new process of trade opening between Colombia and Venezuela